GEOMETRIC FUNCTION (American Journal of Research in Humanities and Social Sciences, 2024)
Geometric functions play a fundamental role in various branches of geometry, providing precise mathematical descriptions of shapes, transformations, and spatial relationships. These functions are essential in defining geometric objects, performing transformations, analyzing properties, modeling physical systems, and solving geometric problems. In complex analysis, geometric functions such as conformal mappings preserve angles and shapes, while in algebraic geometry, they define curves and surfaces through algebraic equations. Transformations like rotations and translations are described using matrix functions. Trigonometric functions relate angles to side lengths in right triangles and are crucial in geometry. Geometric functions also find applications in computer-aided design (CAD) and differential geometry, where they describe shortest paths and curvature. This comprehensive overview highlights the diverse applications and significance of geometric functions in mathematics and its applications.